Enhancing Resilience in Electricity Supply Chains: A SCOR Model Approach for Vertically Integrated Utilities - Imtihan, Najahul; Jaya, Wihana Kirana; Ciptono, Wakhid Slamet; Rendroyoko, Ignatius (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This study introduces an innovative application of the Supply Chain Operations Reference (SCOR) model in a vertically integrated electricity supply chain. In this context, utilities manage all activities from primary energy procurement, generation, and transmission to distribution, which poses unique challenges due to process interdependence. The framework’s comprehensive approach—covering plan, source, make, deliver, return, and enable—serves as a diagnostic and benchmarking tool that enhances supply chain resilience, reliability, responsiveness, flexibility, cost efficiency, and asset management. By aligning standardized supply chain methodologies with the specific requirements of the electricity industry, this study effectively identifies potential bottlenecks and risks across the integrated supply chain. This application differentiates this study from the existing literature and provides new actionable insights for sustainable supply chain management practices in the electricity sector.